News sites psycholinguistics code: collective authorship - Natalia Akimova (Психолінгвістика)
The article deals with the problem of Internet news authorship and its psychological consequences for recipients. The theory about collective authorship in the network is proposed. Linguistic markers to discover collective authorship in news sites are identified. There are examples from runet and ukrnet, particularly several news announcements have been analyzed, comments have been provided that explain inconsistency, fragmentary, surplus multiple meaning of these utterances. The methods of analysis and synthesis, descriptive text analysis, lingvocultural and concept text analysis, modeling, method of semantic and pragmatic interpretations are used to define collective authorship intentions and consequences, to accent speech manipulation, to analyze neurolinguistic understanding mechanisms, Internet discourse impact, to represent manipulative potential of the texts. There are theses in the conclusions: the collective authorship is represented in the Internet news text through imaginary quotation, precedent texts transformation or mechanical combination of several texts with a common comment. The skillful use of collective authorship creates a holistic impression about the day events, sets associations that one news confirmed the another news. But collective authorship mistakes are immediately noticeable, they provoke a critical attitude to the message.